Proceedings of the 4th International Conference on Wireless Mobile Communication and Healthcare - "Transforming Healthcare Thro 2014
DOI: 10.4108/icst.mobihealth.2014.257248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blind Source Separation Algorithms for Optical Heart Rate Monitoring

Abstract: Monitoring of physiological signals of an individual via remote and contactless means is an important scientific challenge, whose resolution will enable the development of novel, nonintrusive mHealth and wellness-management systems and services. In this paper, the performance of three blind source separation algorithms for the optical estimation of the heart rate have been studied. The objective is to perform a comparative evaluation of their accuracy and convergence capability, for the optical estimation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…The results showed that some algorithms (i.e. FastICA, RADICAL) gave better results than other (JADE, Robust ICA) [4,5]. However, in [5] the authors showed that sometimes there were problems with ICA algorithms, for example, FastICA failed to properly initialize.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results showed that some algorithms (i.e. FastICA, RADICAL) gave better results than other (JADE, Robust ICA) [4,5]. However, in [5] the authors showed that sometimes there were problems with ICA algorithms, for example, FastICA failed to properly initialize.…”
Section: Introductionmentioning
confidence: 93%
“…Later, many different ICA algorithms have been evaluated including FastICA, Jade, RADICAL [4]. The results showed that some algorithms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2002 [1]. Since then, many researchers have worked with camera-based photoplethysmography, most often to assess the heart rate [2][3][4][5][6][7][8]. Since the technique is highly sensitive to artifacts, induced by movements and lightening changes, The authors would like to thank the Saxon state ministry of science and culture (SMWK) and the European Union for funding the project CardioVisio -Contactless acquistion of vital parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed techniques use segments of different color channels (typically RGB) extracted from regions of interest (ROI), typically the face, as input to PCA or JADE ICA [4,[9][10][11][12][13][14]. FastICA [15] has also been applied to RGB signals [6,14] and achieved a slightly better performance in comparison to other ICA algorithms [6]. Tsouri et al [16], on the other hand, used RGB information of a face ROI as input for a constrained ICA.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac refractory period ∆t R is considered as 0.3 s [10], whereas the maximum peak-topeak distance ∆t max is considered as 1.5 s (i.e. a minimum heart rate of 45 bpm [13]). Accordingly, a sequence (x) ∈ {0, 1} is obtained by:…”
Section: Spatio-temporal Bss Output Channel (Bss) Including Its Envelmentioning
confidence: 99%